New approaches to the treatment of Age-Related Macular Degeneration (AMD). (August 2022) - Csaky, Karl; Curcio, Christine A.; Mullins, Robert F.; Rosenfeld, Philip J.; Fujimoto, James; Rohrer, Bärbel; Ribero, Ramiro; Malek, Goldis; Waheed, Nadia; Guymer, Robyn; Hageman, Gregory S.; Chen, Hao; et al.
Highlights: Choroid and choriocapillaris are potential important targets of therapy early in AMD. Macular vasculature pathology, like choriocapillaris flow deficits, can be measured using OCT-A. Subretinal drusenoid deposits result from biogenesis pathways involved in lipid homeostasis. How to target (over- or under-express) the HtrA1 gene associated with AMD is controversial. Optimal gene therapies for AMD depend on retinal delivery site and specificity to retinal cell.